Karakter morfologi, biologi, dan molekuler tiga isolat Helicoverpa armigera Nucleopolyhedrovirus (HearNPV) terhadap penggerek buah kapas Helicoverpa armigera Hubner (Lepidoptera: Noctuidae) - Farriza Diyasti; Teguh Santoso; R. Yayi Munara Kusumah (Jurnal Entomologi Indonesia, 2016)
Helicoverpa armigera Hubner (Lepidoptera: Noctuidae) is one of the most important pests on cotton. Yield losses due to this pest can reach up to 70%. Pest control using the NPV has been proven to be effective in the field. However NPV isolates from different geographical locations could be showed variation in genetic and their biology. The purpose of this study was to compare morphology, biology, and molecular characteristics between three HearNPV isolates from cotton field in South Sulawesi, Central Java, and East Java. Scanning electron microscope (SEM) was used to look at morphological characters, whereas biological characters were observed by dipping shelled of young corn cob on each isolate suspension with a density of 2.5 x 103, 2.5 x 104, 2.5 x 105, 2.5 x 106, 2.5 x 107 POBs /ml and control then fed to the first instar larvae of H. armigera. Probit analysis was used to determine LC and LT. The molecular assay used polymerase chain reaction (PCR) with lef-8 gene. The results showed that the three isolates had the shape and size of polyhedra which was not significantly different with the mean diameter were 0.86 μm. The result showed that in 7 days post infection, HearNPV isolate from East Java was the most virulent isolates with the lowest LC50, which is 6.38 POBs/ml, but lowest LT50 value in 2.5 x 107 POBs/ml were showed both from East Java and South Sulawesi, which are 2.7 days post infection. Meanwhile, the DNA sequencing of the three isolates showed a high similarity (100% homology).